PERANAN WEBSITE DALAM MEMEDIASI ETIKA BISNIS BERBASIS KEMANUSIAAN TERHADAP KEPUTUSAN KONSUMEN DARING - Irwan Christanto Edy; Teddy Rahady; Sari Wijayanti (Jurnal Kewirausahaan Bukit Pengharapan, 2022)
Humanitarian-based business ethics is an understanding that emphasizes dignity, dignity, ethics that upholdhuman values. Human values are related to business life. The purpose of this study is to verify the role model ofhumanitarian-based ethics in online consumers. This study used a population, namely the millennial generation in thecity of Surakarta. Research using the surve method. Data collection instruments with online questionnaires. Thenumber of respondents obtained was 100 people. Data collection techniques with convenience sampling. Samples aretaken/selected because they are in the right place and time. Indicators of humanitarian-based business ethics includehonesty, openness, justice, religious and social society. Instrument testing using validity and reliability. Statisticalanalysis with SEM-PLS due to the assumption that the data is not normally distributed. The results show that 1)humanitarian-based business ethics positively affects websites, 2) humanitarian-based business ethics positivelyaffects online shopping decisions, 3) Websites positively affect online decisions. The main finding in this study is thathumanitarian-based business ethics has a positive influence on consumers' online decisions mediated by websites.Keyword : Humanitarian-based business ethics, Website, Online Decisions, Electronic Commerce (E-commerce)